Torsion as alternative to curvature in the description of gravitation - De Andrade, V. C.; Arcos, H. I. [UNESP]; Pereira, J. G. [UNESP] (My University, 2004)
The general covariance principle, seen as an active version of the principle of equivalence, is used to study the gravitational coupling prescription in the presence of curvature and torsion. It is concluded that the coupling prescription determined by this principle is always equivalent with the corresponding prescription of general relativity. An application to the case of a Dirac spinor is made.